2003
DOI: 10.1002/bit.10759
|View full text |Cite
|
Sign up to set email alerts
|

Oscillating perfusion of cell suspensions through three‐dimensional scaffolds enhances cell seeding efficiency and uniformity

Abstract: We developed a bioreactor for automated cell seeding of three-dimensional scaffolds by continuous perfusion of a cell suspension through the scaffold pores in oscillating directions. Using quantitative biochemical and image analysis techniques, we then evaluated the efficiency and uniformity of perfusion seeding of Polyactive foams as compared to conventional static and spinner flask methods. Finally, we assessed the efficacy of the perfusion seeding technique for different scaffolds and cell types. Perfusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
374
3
17

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(414 citation statements)
references
References 37 publications
20
374
3
17
Order By: Relevance
“…Differences in geometrical configurations of perfusion bioreactor systems and the complex internal architecture of scaffolds (Bancroft et al, 2002;Bonvin et al, 2010;Wendt et al, 2003;Zhao and Ma, 2005) makes correlating observed biological outcomes on the basis of inlet fluid flow-rate very difficult. Calculation of the  within systems allows comparisons to be made on a single representative scale.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in geometrical configurations of perfusion bioreactor systems and the complex internal architecture of scaffolds (Bancroft et al, 2002;Bonvin et al, 2010;Wendt et al, 2003;Zhao and Ma, 2005) makes correlating observed biological outcomes on the basis of inlet fluid flow-rate very difficult. Calculation of the  within systems allows comparisons to be made on a single representative scale.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we adapted the methods established by Wendt et al 21 for cell seeding onto PGS by perfusion of a cell suspension through the scaffold voids. We determined the proper flow rate to use in order to achieve a dense, uniform spatial distribution of cells throughout the scaffolds.…”
Section: Cultivation Of Cardiac Tissue Constructs With Culture Mediummentioning
confidence: 99%
“…More homogeneous [200] or less uniform cell distribution [199] was also observed. Perfusion seeding increased the cell seeding efficiency and uniformity [199]. In our studies, static seeding on CM scaffolds was inefficient and not homogeneous.…”
Section: Ebcell Ebsmentioning
confidence: 80%
“…Some studies claim more efficient seeding [198], whereas others found lower seeding efficiency in a spinner flask compared to static seeding [199,200]. More homogeneous [200] or less uniform cell distribution [199] was also observed. Perfusion seeding increased the cell seeding efficiency and uniformity [199].…”
Section: Ebcell Ebsmentioning
confidence: 99%